2017
DOI: 10.1038/nature23674
|View full text |Cite
|
Sign up to set email alerts
|

A spin transition mechanism for cooperative adsorption in metal–organic frameworks

Abstract: Cooperative binding, whereby an initial binding event facilitates the uptake of additional substrate molecules, is common in biological systems such as haemoglobin. It was recently shown that porous solids that exhibit cooperative binding have substantial energetic benefits over traditional adsorbents, but few guidelines currently exist for the design of such materials. In principle, metal-organic frameworks that contain coordinatively unsaturated metal centres could act as both selective and cooperative adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
208
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(217 citation statements)
references
References 29 publications
6
208
0
3
Order By: Relevance
“…16 These phenomena are of fundamental interest and form the basis of various applications including chemiresistive sensors, 11,17,18 fluorescence sensors, 19 and cooperative adsorption. 13,16 Although several strategies are effective for increasing the electrical conductivity in MOFs, 20,21 among the most promising, and certainly more tractable synthetically, are those that involve post-synthetic doping. Guest molecules introduced after the formation of a MOF may tune either the charge mobility or the charge density in the skeleton of a given material, allowing in either case continuous enhancement of electrical conductivity over several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 These phenomena are of fundamental interest and form the basis of various applications including chemiresistive sensors, 11,17,18 fluorescence sensors, 19 and cooperative adsorption. 13,16 Although several strategies are effective for increasing the electrical conductivity in MOFs, 20,21 among the most promising, and certainly more tractable synthetically, are those that involve post-synthetic doping. Guest molecules introduced after the formation of a MOF may tune either the charge mobility or the charge density in the skeleton of a given material, allowing in either case continuous enhancement of electrical conductivity over several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic properties may be modulated either inherently, through changes in chemical composition, or through hostguest interactions. Guest molecules may cause structural variation, 8,9 tune electrical conductivity, 10,11 induce spin state transitions, 12,13 modulate luminescence wavelength, 14,15 and even participate in guest-guest interactions. 16 These phenomena are of fundamental interest and form the basis of various applications including chemiresistive sensors, 11,17,18 fluorescence sensors, 19 and cooperative adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…[89] The penetration of gas through ZIF-8 membranes can also be switched using an external electric field. [90] Magnetic phase transitions have been investigated on a theoretical level for 2D MOFs with a range of metallic centers (Cr, Mn, Fe, Co, Ni), [91] particularly, phase transition between homogeneous ferromagnetic and spin-forming antiferromagnetic states. [82] In addition, selective adsorption of CO was demonstrated for 3D MOFs with coordinated unsaturated iron (II) sites, based on the spin state transition of the iron (II) sites.…”
Section: Phase-change Effectmentioning
confidence: 99%
“…[8] This separation process is challenging owing to the similar physical properties of both gases.For separation of CO,ahighly selective but nevertheless reversible adsorption is needed. [14] Asynthetic stevensite with ahomogeneous charge density (formula unit:N a 0.94(6) [Mg 5.18(10) Li 0.34(6) ]Si 8 O 20 F 4 ) [3i] was pillared with 1,4-dimethyl-1,4-diazabicyclo[2.2.2]octane (Me 2 DABCO 2+ )t oo btain the microporous hybrid material (MOPS-5) with an arrow pore size distribution and micro-[*] Dr.M .M.H erling, [+] M. Rieß, [+] Dr. To date CO is mostly separated by chemisorption on transitionmetal ions such as Cu +, which however requires ac ostintensive,endergonic release of CO. [12] Sato et al for example recently reported as elf-accelerating CO sorption in as oft nanoporous material with selective CO adsorption on aCu 2+ -PCP.…”
Section: Microporousmaterialswereinitiallydominatedbyzeolitesmentioning
confidence: 99%
“…[5] Forthis reason, the charge density of the host must be homogenous to obtain narrow pore size distributions.G iven that this requirement is met, in turn the two-dimensional (2D) pore system of MOPS can be finetuned by adjusting the layer charge of host layers and the charge,s ize,a nd shape of the pillar. [14] Asynthetic stevensite with ahomogeneous charge density (formula unit:N a 0.94(6) [Mg 5.18(10) Li 0.34(6) ]Si 8 O 20 F 4 ) [3i] was pillared with 1,4-dimethyl-1,4-diazabicyclo[2.2.2]octane (Me 2 DABCO 2+ )t oo btain the microporous hybrid material (MOPS-5) with an arrow pore size distribution and micro-[*] Dr.M .M.H erling, [+] M. Rieß, [+] Dr. [7] In many large-scale industrial oxidation processes,C Oi s produced, which has to be separated from N 2 for chemical processing.…”
mentioning
confidence: 99%